Acute Effects of the Wim Hof Breathing Method on Repeated Sprint Ability: A Pilot Study - Citherlet, Tom; Crettaz von Roten, Fabienne; Kayser, Bengt; Guex, Kenny (Frontiers in Sports and Active Living, 2021)
The Wim Hof breathing method (WHBM) combines periods of hyperventilation (HV) followed by voluntary breath-holds (BH) at low lung volume. It is increasingly adopted by coaches and their athletes to improve performance, but there is no published research on its effects. We determined the feasibility of implementing a single WHBM session before repeated sprinting performance and evaluated any acute ergogenic effect. Fifteen amateur runners performed a single WHBM session prior to a Repeated Ability Sprint Test (RAST) in comparison to voluntary hyperventilation (HV) or Spontaneous Breathing (SB) (control) in a randomized cross-over design. Gas exchange, heart rate and finger pulse oxygen saturation (SpO2) were monitored. Despite large physiological effects in SpO₂ and VCO₂ levels of both HV and WHBM, no significant positive or negative condition effects were found on RAST peak power, average power, or fatigue index. Finger SpO2 dropped to 60 ± 12% at the end of the breath holds. Upon the last hyperventilation in the WHBM and HV conditions, end-tidal CO2 partial pressure (PETCO2) values were 19 ± 3 and 17 ± 3 mmHg, indicative of respiratory alkalosis with estimated pH increases of + 0.171 and of + 0.181, respectively. Upon completion of RAST, 8 min cumulated expired carbon dioxide volumes in WHBM and HV were greater than in SB, suggesting lingering carbon dioxide stores depletion. These findings indicate that despite large physiological effects a single WHBM session does not improve anaerobic performance in repeated sprinting exercise.